The Role of Probiotics in Preventing Post-Appendectomy Complications in Obese Child: A Case Report - Tasya Khalis Ilmiani; Efry Theresia Sianturi; Musyayyadah Musyayyadah; Tutik Ernawati (Riviera Publishing, 2025)
Appendicitis is an inflammation of the appendix that often occurs in children. Appendectomy is the primary treatment. Obese children have a higher risk of having post-operative complications. Probiotics play a role in maintaining a balanced gut flora, potentially accelerating post-operative recovery. Case: A 12-year-old boy, weighing 50 kg, standing 140 cm tall, and with a BMI of 25.5 kg/m² (above the 95th percentile according to the CDC 2000), was diagnosed with acute appendicitis and underwent a laparoscopic appendectomy. On the first postoperative day, the patient experienced constipation and abdominal distension. He received a total energy intake of 1,300 kcal/day and was given two sachets of probiotics (Lactobacillus acidophilus, Bifidobacterium longum, and Streptococcus thermophilus) daily. On the third day, his abdominal distension decreased, and his bowel pattern improved. Discussion: Obesity causes changes in the gut microbiota, increases inflammation, and slows gut motility and wound healing. Studies show that a combination of probiotics can lower the risk of constipation and post-operative infection. The motility of the gastrointestinal tract can improve, and the inflammation will reduce. Probiotics also play a role in gut health by increasing the production of short-chain fatty acids. In this case, probiotic administration is supporting its use in post-appendectomy recovery in obese children by showing a rapid symptom improvement. Conclusion: Probiotics can help accelerate post-appendectomy recovery in obese children by balancing the gut microbiota, reducing inflammation, and improving gut motility.